Nordic Fauna at the Biological Museum, Skansen (Stockholm) - Anders Telenius; Lars-Erik Larsson; Boel Recén (GBIF Sweden, 2026)
The collections of specimens at the Biological Museum, Stockholm, SwedenThe dataset covering the collection of the Biological Museum in Stockholm contains information about all extant specimens kept and presented in the museum´s exhibition, intended to portray “Nordic fauna in its natural surroundings” to visitors. Opened in 1893 in a purpose-built house, Nordic vertebrates (excluding fishes) are mounted and displayed in natural poses, placed in a 360-degree cyclorama amongst dried vegetation and fake terrain elements in front of a huge background wall-painting executed by the famous Swedish painter Bruno Liljefors.Mostly consisting of birds but also large, and some smaller mammals of Scandinavia, the original specimens and early additions and replacements were mounted in the atelier of the renowned wildlife hunter and taxidermist Gustaf Kolthoff (1845-1913). To the necessary extent, where pest insects have attacked the animals, certain successive replacements have been made, new animals then notably being brought in and mounted by taxidermists at “Kolthoffs naturaliemagasin”, and by Werner Berg, Birger Nordahl et al. (Swedish Museum of Natural History) during the mid-to late 19-hundreds. Some of the most recent specimens (mounted by Nicklas Svensson) were added during the last decade of the 20th century. The museum was thoroughly renovated in 1992 but remains intact from all other major aspects thus strongly representing a late 19th century view of nature and its inhabitants. It is presently undergoing a more extensive renovation aiming at presenting the 19th century cyclorama as when inaugurated.Since no catalogue of the museum´s specimens was ever kept, all information regarding the place of origin, time of collection, collector, acquisition and any additional information have been inferred from some (but very few!) specimen labels, and (primarily) from cross-tabulation of the written contents of a great number of successive editions of exhibit´s descriptions (printed booklets), from invoices, from mail conversation between the museum management and taxidermists, from informal notes and from interviews with former employees and informants.All animals were collected in their representative parts of Scandinavia including those found and brought back during a series of late 19th century, and early 20th century expeditions to Svalbard and Greenland (the latter presented in two separate, smaller dioramas. The latter animals were considered as “Nordic” representing North Atlantic and Polar Sea habitats under Nordic governance, and detailed expedition´s reports provide the most detailed information available on the provenance of these specimens.N.b. The contents of this dataset is simultaneously published by Digitalt Museum (https://digitaltmuseum.se/), serving Swedish and Norwegian cultural heritage institutions.
Keywords: Nordic fauna; Birds; Mammals; 19th century; Cyclorama exhibition; OCCURRENCE; Biological Sciences; Biologi